Run by Crawling (the “Cockroach” Topic in Russian Literature Nineteenth– Early Twentieth Century and in Mikhail Bulgakov’s Works) - Yablokov, Evgeniy (Porównania, 2021)
The article deals with the insect discourse of Mikhail Bulgakov’s works (the story Cockroach, plays The Flight and Adam and Eve) in comparison with the Russian literary tradition of the nineteenth–twentieth century. The development of the “cockroach” topic is traced in the writer’s works of the mid 1920s. In particular, the role of the story “Cockroach” was analyzed in context of the concept (plan) of the play The Flight. The “Cockroach” motifs in Bulgakov’s works are compared with the plots of a number of his predecessors and contemporaries in literature – Ivan Myatlev, Fedor Dostoevsky, Ieronim Yasinsky, Maxim Gorky, Arkady Averchenko, Korney Chukovsky, Yevgeny Zamyatin, Boris Lavrenyov and others. A comparative analysis allows for a deep understanding of the role of the insect code in Bulgakov’s poetics, and to introduce significant refinements to the interpretation of many of his works.